Extreme heat-related mortality avoided under Paris agreement goals - Mitchell, D; Heaviside, C; Schaller, N; Harrington, L; Allen, M; Ebi, K; Fischer, E; Gasparrini, A; Kharin, V; Shiogama, H; Sillmann, J; Sippel, S; et al. (Springer Nature, 2018)
In key European cities, stabilising climate at 1.5◦C would decrease extreme heat-related mortality by 15-22% per summer compared with stabilisation at 2◦C.